Expedient synthesis of 1,2,3-triazole-fused tetracyclic compounds by intramolecular Huisgen ('click') reactions on carbohydrate-derived azido-alkynes - Hotha, Srinivas; Anegundi, Ramakrishna I.; Natu, A. A. (Tetrahedron Letters, 2005)
An efficient, practical and convenient synthesis of 1,2,3-triazole-fused tetracyclic compounds was achieved by intramolecular 1,3-dipolar cycloaddition of carbohydrate-derived azido-alkynes. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: carbohydrates; Click chemistry; Cycloaddition; diversity oriented synthesis; Huisgen reaction

Synthesis of 1,2,3-triazole and 1,2,3,4-tetrazole-fused glycosides and nucleosides by an intramolecular 1,3-dipolar cycloaddition reaction - Anegundi, Ramakrishna I.; Puranik, Vedavati G.; Hotha, Srinivas (Organic & Biomolecular Chemistry, 2008)
Various 1,2,3-triazole and 1,2,3,4-tetrazole fused multi-cyclic compounds were synthesized from carbohydrate derived azido-alkyne and azido-cyanide substrates. The acid sensitive 1,2-O-isopropylidene group of the furanosyl sugar was utilized for diversification to glycosides and nucleosides under Fischer glycosidation and Vorbruggen's conditions, respectively.